A computational study of vortex shedding from a NACA-0012 airfoil at high angles of attack. (2018) - Zakaria, Mohamed Y.; Ibrahim, Mostafa M.; Ragab, Saad; Hajj, Muhammad R.
A numerical investigation of the two-dimensional flow over a NACA-0012 wing section is conducted at Reynolds number of 79, 900 over a range of angles of attack between zero and 40 degrees. The performance of different turbulence models in terms of capturing flow separation and transition, and vortex shedding at 40 degrees is determined. Three turbulence models, namely the Spalart-Allmaras (SA), modified Spalart-Allmaras, and Reynolds stress transport model and a simulation without a turbulence model (laminar flow) are conducted. The results show that the lift and drag coefficients predicted by the Spalart-Allmaras model are in good agreement with experimental data; with small differences over angles of attack larger than 25 degrees. The Reynolds stress transport model and laminar flow calculations predict vortex shedding from the leading and trailing edges and formation of a vortex street in the wake. On the other hand, simulations using the Spalart-Allmaras and modified Spalart-Allmaras models do not predict such a vortex wake and that may be due to over-diffusion of shed vortices. Power spectral densities of the unsteady lift, drag and velocity are used to determine flow characteristics and their relation to the forces.